Affairs of the heart - Wahhaj, Siraj; One Islam Publications; Mecca Centric Da'wah Group; Muslim Support Group (N.S.W, Australia : One Islam Publications, 2006)
Imam Siraj Wahhaj teaches the high school and college students in attendance that they must be well-rounded individuals with a foundation rooted firmly in the spiritual aspect of themselves
Title from title screen
Presenter : Siraj Wahhaj
Keywords: Religious life -- Islam; Islam